Determination of Meloxicam Using Direct and Indirect Flow Injection Spectrophotometry - Abed, Ream I.; Hadi, Hind (Current Pharmaceutical Analysis, 2021)
Background: Meloxicam is a non-steroidal anti-inflammatory drug, known to inhibit cyclooxygenase, a key enzyme of prostaglandin biosynthesis at the site of inflammation. Objectives: Two sensitive and fast spectrophotometric methods (direct and indirect) using flOW INJection Analysis (FIA) have been described for the assay of meloxicam in pure and in pharmaceutical formulations. Methods: The direct method (method A) depended on the coupling of meloxicam with diazotized procaine benzylpenicillin in alkaline medium. In contrast, the indirect method (method B) involved a charge transfer reaction between the alkaline hydrolytic product of meloxicam as n-donor with metol (p-methylaminophenol sulfate) as a π- acceptor using sodium periodate as an oxidant. Results: The colored products exhibited absorption maxima at 492 and 656 nm for method A and B respectively. The methods obeyed Beer’s low over concentration ranges of 5-80 and 15-225 μg/mL, respectively. The detection limits were 2.73 and 5.26 μg/mL for direct and indirect methods, respectively. The chemical and physical parameters associated with FIA manifolds were optimized to construct the most sensitive and reproducible results. Conclusion: Methods described herein are cheap, environmentally friendly and showed no significant difference with those of the official method indicated no significant difference in accuracy and precision.
Keywords: charge transfer reaction